An assessment of gynecological manifestations in women with female genital schistosomiasis with reference to Schistosoma biomarkers, sexually transmitted infections and bacterial vaginosis - Randrianasolo, Bodo Sahondra; Jøker, Karoline; Arenholt, Louise Thomsen Schmidt; Rabozakandraina, Tiana Onintsoa Oliva; Ramarokoto, Charles Emile; Brønnum, Dorthe; Jensen, Martin; Christensen, Søren Lundbye; Jensen, Jørgen Skov; Corstjens, Paul; van Dam, Govert J.; Kobayashi, Noriko; et al. (Frontiers in Tropical Diseases, 2024)
BackgroundAlthough a variety of different gynecological manifestations have been reported in women with female genital schistosomiasis (FGS), causality remains to be established. This study aimed to evaluate the gynecological manifestations in women with FGS in accordance with the status of Schistosoma biomarkers, sexually transmitted infections (STIs), and bacterial vaginosis (BV).MethodsThe study was conducted in an endemic Schistosoma haematobium (Sh) area in northern Madagascar in conjunction with a randomized controlled trial investigating the effects and safety of a praziquantel repeated-dosing regimen for women with FGS-associated cervical lesions. Urogenital complaints, pelvic exam abnormalities, and cervical lesion types were assessed in relation to cervicovaginal Schistosoma DNA, circulating anodic antigen (CAA) in serum, and urinary Sh egg count, in addition to STIs and BV.ResultsAmong the included 116 women with a median of 26 years (range 15 to 35), the distribution of Schistosoma DNA and CAA outcomes, specified as either positive (+) or negative (-), were as follows: +/+ (18.1%), +/- (0%), -/+ (58.6%), and -/- (23.3%). Of the three Schistosoma biomarkers, only Schistosoma DNA and the urogenital complaint of blood in the urine were significantly associated. None of the biomarkers were significantly associated with pelvic exam abnormalities or cervical lesions. Sixty women (52.6%) were diagnosed with STIs and/or BV. A positive status was not significantly associated with any of the gynecological manifestations, except BV and homogeneous yellow sandy patches.ConclusionIt remains uncertain whether biomarkers such as cervicovaginal Schistosoma DNA, serum CAA, and Schistosoma eggs in urine adequately cover the full spectrum of gynecological manifestations reported in women with FGS, including urogenital complaints, pelvic exam abnormalities, and cervical lesions. Moreover, it seems difficult to determine the origin of the different manifestations due to the common co-existence of STIs and/or BV as potential confounders.